Periclase and forsterite composite material as well as preparation method and application thereof
By mixing the moisture tail mines and hydrophilic magnesium bricks in a common grinding, prepare the composite materials of magnesium magnesium olives, solve the problem of the low value of magnesium brick water absorption and expansion and floating tailings, improve the performance of the material and The utilization rate of hydraulic magnesium bricks.
Patent Information
- Application Number
- CN202411988345.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing magnesium bricks absorb water and expand in humid environments, resulting in a decrease in compressive strength and flexural strength, affecting the performance of refractory materials. At the same time, high-grade magnesites are difficult to meet the needs of high-quality magnesium refractory materials, and the flotation process produces a large number of low-value flotation tailings.
Use diamond -magnesium ore tailings and hydrated magnesium bricks for wet mixing and grinding. Magnesium magnesium magnesium olives composite materials are prepared by craftsmanship such as filtration, vacuum squeeze, drying, and sintering, and optimizing raw materials to improve material performance Essence
The problem of low mixing uniformity and poor performance of magnesium olives has been solved, and the utilization and added value of hydrophilic magnesium bricks are improved. , Extend the service life.
Smart Images

Figure CN119371219A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a periclase-forsterite composite material and a preparation method and application thereof. Background Art
[0002] With the large-scale mining of magnesite, high-grade ore sources are becoming increasingly exhausted. High-grade magnesite can hardly meet the demand for the preparation of high-quality magnesia refractory materials. At present, more and more companies have begun to use flotation technology to improve the purity of magnesium oxide (MgO) in magnesite. However, the flotation process will produce a large amount of 40%~50% flotation tailings, MgO content of 35%~45%, SiO2 content of 20%~30%, and ignition loss of about 25%~35%.
[0003] Magnesia bricks are easy to absorb water and expand when placed outdoors or in a humid environment for a long time. This not only affects the appearance of the magnesia bricks, but also affects the physical and chemical properties of the refractory materials. In particular, after the magnesia bricks absorb water and expand, their compressive strength and flexural strength will be significantly reduced, thus affecting the use of the refractory materials.
[0004] Forsterite has the advantages of high melting point, low thermal expansion coefficient, good chemical stability, etc. It is an excellent alkaline refractory material. Magnesium-aluminum spinel is the only intermediate compound in the MgO-Al2O3 binary system. It has good erosion resistance, corrosion, strong spalling ability, good slag resistance, abrasion resistance, good thermal shock stability, high temperature resistance and other performance characteristics. It is an ideal raw material for the production of magnesia-aluminum spinel bricks, ladle lining bricks, ladle castables and other refractory products for high temperature zone of cement rotary kiln.
[0005] The hydration of magnesia bricks is mainly the reaction of magnesium oxide with water and carbon dioxide in the air to form magnesium hydroxide and magnesium carbonate on the surface of magnesia bricks, which leads to the failure of refractory materials. First, the surface of magnesium oxide will absorb water molecules to form positively charged magnesium hydroxide ions (MgOH + ) and releases hydroxide ions (OH — Then, magnesium hydroxide ions begin to dissolve, further generating magnesium ions (Mg 2+ ) and hydroxide ions. The dissolved magnesium ions combine with the hydroxide ions in the solution to form magnesium hydroxide (Mg(OH)2) precipitation. This is a key step in the hydration process of magnesia bricks, because magnesium hydroxide is one of the main components of the hydration layer of magnesia bricks. In addition, magnesium oxide will react with carbon dioxide in the air to form magnesium carbonate (MgCO3). This reaction will also form a layer of hydrated layered material on the surface of magnesia bricks, which will seriously affect the performance of magnesia bricks. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a periclase-forsterite composite material and a preparation method and application thereof.
[0007] In the first aspect, the preparation method of the periclase forsterite composite material provided by the present invention comprises: wet mixing and grinding the magnesite flotation tailings and hydrated magnesia bricks, and then filtering, vacuum squeezing, drying and sintering; the mass ratio of the magnesite flotation tailings and the hydrated magnesia bricks is 60:40~90:10. The novel preparation method of the periclase forsterite composite material using the magnesite flotation tailings and hydrated magnesia bricks provided by the present invention solves the problems of low mixing uniformity and poor performance of forsterite, and also alleviates the problems of low utilization rate and low added value of hydrated magnesia bricks. The raw materials can be better mixed and the pretreatment of the tailings can be reduced by wet mixing and grinding, and the periclase forsterite composite material can be better prepared by process optimization. In particular, by optimizing the addition ratio of the magnesite flotation tailings and hydrated magnesia bricks, high-quality periclase forsterite composite materials can be better prepared.
[0008] Preferably, the mass ratio of the magnesite flotation tailings to the hydrated magnesia bricks is 65:35-87:13, preferably 65:35. The use of the magnesite flotation tailings and hydrated magnesia bricks in the preferred ratio can further improve the ratio of forsterite and periclase in the periclase forsterite composite material, so that the prepared material has better performance.
[0009] Preferably, in the magnesite flotation tailings, the mass content of MgO is 38% to 40%, and the mass content of SiO2 is 24% to 26%; in the hydrated magnesia bricks, the mass content of MgO, Mg(OH)2 and MgCO3 is 80% to 90% in terms of MgO. According to the present invention, the hydrated magnesia bricks are magnesia brick products that are placed in a humid environment and hydrated. The water content in the hydrated magnesia bricks is not limited, for example, it can be 0 to 10%, and the mass content of SiO2 is 0 to 2%. In the present invention, the ratio of raw materials used in the periclase forsterite composite refractory material is affected by magnesium oxide and silicon oxide in the raw materials, and the ideal ratio is achieved by blending, and the effect is better under the preferred ratio and raw materials.
[0010] It is further preferred that the method further comprises the step of pre-treating the hydrated magnesia brick, wherein the pre-treating comprises crushing and / or ball milling the hydrated magnesia brick; preferably, the particle size of the pre-treated hydrated magnesia brick is less than 1 mm. In the present invention, the flotation tailings of magnesite are preferably not crushed, but directly wet-mixed and co-milled with the crushed hydrated magnesia brick.
[0011] Further preferably, the speed of the wet mixing and grinding is 25~150r / min, and the time is 0.5~4h. In the present invention, the wet mixing and grinding preferably adopts the grinding method of ball milling, and the ball milling time includes but is not limited to 0.5~4h, such as 0.5h, 1h, 1.5h, 2.5h, 3h, 3.5h, 4h, etc. and any value therebetween, preferably 2h. The speed includes but is not limited to 25~150r / min, such as 28r / min, 40r / min, 50r / min, 65r / min, 80r / min, 120r / min, etc. and any value therebetween. Preferably, the raw material is placed in a ball milling jar and water is added, and the ball milling is carried out for 2±1h at a speed of 60±20r / min. The amount of water added during the wet mixing process can adopt the appropriate amount commonly used in the art, and the present invention is not limited thereto.
[0012] Preferably, the filtration comprises using a filter press to discharge water added during the wet mixing ball milling process; and / or, the vacuum mud squeezing comprises using a vacuum mud squeezer to squeeze and cut the filter cake into brick blanks; and / or, the drying comprises dehydrating and drying the brick blanks after the vacuum mud squeezing by vacuum drying or air drying.
[0013] Preferably, the sintering includes a step of secondary calcination; preferably, it includes heating to 190-200°C at a rate of 13-15°C / h, then heating to 600-900°C at a rate of 20-25°C / h and keeping warm for 6-8h, then heating to 1350-1450°C at a rate of 25-30°C / h, and then heating to 1500-1650°C at a rate of 18-20°C / h for high temperature calcination; the calcination and holding time is 2-10h.
[0014] Further preferably, the sintering preparation of periclase forsterite-based raw materials is secondary calcined in a tunnel kiln, the calcination temperature is first raised to 200°C at a rate of 15°C / h, and then raised to 900°C at a rate of 25°C / h for 8h, at which time the forsterite-based material reacts violently, and 8h of heat preservation can effectively prevent the material from bursting; then the temperature is raised to 1450°C at a rate of 30°C / h, and then raised to 1500~1650°C at a rate of 20°C / h for high-temperature calcination, preferably 1600°C; the calcination and heat preservation time is, for example, but not limited to, 2~10h, preferably 8h. At this time, it is helpful for the periclase forsterite material to be tightly combined and make the material more dense.
[0015] Preferably, the method for preparing the periclase-forsterite composite material comprises: 1) Crushing: crush the hydrated magnesia bricks, preferably to a particle size less than 1 mm.
[0016] 2) Wet mixing and grinding: the crushed hydrated magnesia bricks are mixed with the magnesite flotation tailings and wet-grinded to obtain a ground raw material. The grinding concentration is preferably 60% to 80%; the grinding fineness is preferably 200 to 400 meshes.
[0017] 3) Dehydration: The wet mixed and ground raw materials are filtered and dehydrated to obtain a raw material filter cake.
[0018] 4) Vacuum extrusion: The raw material filter cake is preferably formed and cut by a vacuum extruder to obtain a periclase-forsterite composite material wet blank.
[0019] 5) Drying: drying the periclase-forsterite composite material wet blank to obtain a periclase-forsterite composite material blank.
[0020] 6) Firing: sintering the periclase-forsterite composite material blank.
[0021] The method for preparing a periclase-forsterite composite material by using magnesia tailings provided by the present invention uses magnesia tailings and hydrated magnesia bricks as raw materials, wherein the (magnesia) tailings raw materials are magnesite flotation tailings. The method of the present invention mainly utilizes the characteristics of magnesite flotation tailings being rich in magnesium oxide and silicon oxide, and utilizes the characteristics of hydrated magnesia bricks being rich in magnesium oxide, magnesium hydroxide and magnesium carbonate. The periclase-forsterite composite material is prepared under a certain pre-mixing ratio. In the present invention, the hydrated magnesia bricks are crushed, and then mixed with the raw material of magnesite flotation tailings in proportion, and then wet mixed and ground, filtered, vacuum extruded, dried and high-temperature controlled crystal phase sintered to directly prepare the periclase forsterite composite material. Preferably, the magnesite flotation tailings and the hydrated magnesia bricks are put into a ball mill for wet mixed and ground; the wet mixed mixture is filtered through a filter press to discharge water in the mixture; the raw material after the filter is vacuum extruded through a mud extruder and cut into shape; the formed raw material is dehydrated and dried by a tunnel dryer; the dried sample is subjected to the temperature rise rate and the heat preservation time at different temperatures to make the magnesium oxide and silicon oxide in the raw material react more fully, so as to prepare the high-quality periclase forsterite composite material.
[0022] In a second aspect, the periclase-forsterite composite material provided by the present invention is prepared by the above-mentioned preparation method.
[0023] In a third aspect, the present invention provides a periclase-forsterite composite material prepared by the above-mentioned preparation method or an application of the above-mentioned periclase-forsterite composite material in the preparation of refractory materials.
[0024] The present invention makes full use of the main components of flotation tailings, MgO and SiO2, and prepares periclase-forsterite composite materials in combination with MgO, Mg(OH)2 and MgCO3 in hydrated magnesia bricks. The periclase-forsterite composite material can be used as a refractory raw material and can be applied to the working lining of a high-temperature kiln with a temperature below 1500°C. On the basis of preserving the low thermal conductivity and excellent alkali corrosion resistance of olivine itself, the wear resistance and corrosion resistance of the material are improved and the service life is extended. The present invention provides a way to explore the high-value utilization of flotation tailings and hydrated magnesia bricks, and can be mass-produced. According to the physical and chemical properties of the flotation magnesia tailings, magnesite, especially low-grade magnesite tailings, is recycled and utilized, and hydrated waste magnesia bricks are recycled and utilized. Not only does it improve the environment, achieve zero discharge of magnesite resources, and recycle hydrated magnesia bricks, but it also further reduces the production cost in the application field, which is of great significance.
[0025] The beneficial effects of the present invention are at least as follows: the present invention provides a method for directly preparing a periclase-forsterite composite material by using flotation tailings and hydrated magnesia bricks, which solves the restriction that the flotation tailings need to be pretreated in the traditional technology and improves the utilization rate of magnesia ore resources. The present invention alleviates the accumulation pressure of magnesia ore tailings, alleviates environmental pressure, and promotes the green recycling and efficient utilization of secondary resources. Moreover, the tailings cost is low, and the operation process of using tailings to prepare forsterite is simple, and it is easy to realize large-scale production. The present invention also alleviates the problem of low utilization rate and difficult recovery of hydrated magnesia bricks, and improves the utilization rate of hydrated magnesia bricks. A tailings treatment process provided by the present invention effectively solves the problem of uneven and unstable tailings composition, and ensures that the obtained periclase-forsterite composite material has stable performance and reliable quality. The present invention utilizes the synthesis mechanism of forsterite to provide a high-temperature controllable crystal phase sintering, and ensures that the obtained periclase-forsterite composite material has stable crystal phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The process flow chart of an embodiment of the present invention.
[0028] Figure 2 This is the XRD spectrum of the sample of Example 4 of the present invention.
[0029] Figure 3 These are the morphological characteristics of the sample of Example 4 of the present invention.
[0030] Figure 4 This is a differential thermal gravimetric curve of the sample of Example 4 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0033] If no specific technology or conditions are specified in the examples of the present invention, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The experimental reagents and raw materials involved are all commercially available, and the reagents are all analytically pure products.
[0034] In the embodiment of the present invention, the size of the periclase forsterite brick formed after cutting is 240 mm×115 mm×53 mm.
[0035] In the following examples of the present invention, the components of the magnesite tailings and hydrated magnesia bricks used are shown in Table 1.
[0036] Table 1 Material composition of magnesite tailings and hydrated magnesia bricks (%)
[0037] Example 1
[0038] This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, the process is as follows: Figure 1 As shown, the specific operations are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 87:13.
[0039] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0040] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0041] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0042] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0043] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0044] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 15℃ / h, then heat it to 900℃ at a rate of 25℃ / h and keep it warm for 8h, then heat it to 1450℃ at a rate of 20℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 8h at a heat preservation time, and get the final product by cooling in the furnace.
[0045] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.69g / cm 3 , water absorption rate is 8.6%.
[0046] Comparative Example 1 This comparative example provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific operation is as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 100:0.
[0047] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0048] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0049] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0050] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0051] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 15℃ / h, then heat it to 900℃ at a rate of 25℃ / h and keep it warm for 8h, then heat it to 1450℃ at a rate of 30℃ / h, and then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 8h at a heat preservation time, and get the final product by cooling in the furnace.
[0052] After testing, the performance indicators of the periclase forsterite composite material prepared in this comparative example are: volume density 2.53g / cm 3 , water absorption rate is 17.2%.
[0053] Example 2 This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific operations are as follows: Weighing: weigh the magnesite flotation tailings and hydrated magnesia bricks required for the sample, wherein the mass ratio of the magnesite flotation tailings and hydrated magnesia bricks is 80:20.
[0054] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0055] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0056] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0057] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0058] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0059] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 15℃ / h, then heat it to 900℃ at a rate of 20℃ / h and keep it warm for 8h, then heat it to 1450℃ at a rate of 30℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 8h at a heat preservation time, and get the final product by cooling in the furnace.
[0060] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.72g / cm 3 , water absorption rate 7.9%.
[0061] Example 3 This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 72:28.
[0062] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0063] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0064] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0065] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0066] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0067] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 10℃ / h, then heat it to 900℃ at a rate of 25℃ / h and keep it warm for 8h, then heat it to 1450℃ at a rate of 20℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 10h and cool it in the furnace to obtain the final product.
[0068] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.70g / cm 3 , water absorption rate 6.5%.
[0069] Example 4 This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 65:35.
[0070] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0071] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0072] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0073] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0074] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0075] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 10℃ / h, then heat it to 900℃ at a rate of 25℃ / h and keep it warm for 8h, then heat it to 1450℃ at a rate of 20℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 10h and cool it in the furnace to obtain the final product.
[0076] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.73g / cm 3 The XRD spectrum, morphology and differential thermal gravimetric curve of the periclase-forsterite composite material are as follows: Figures 2~4 shown.
[0077] Example 5 This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 50:50.
[0078] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0079] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0080] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0081] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0082] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0083] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 10℃ / h, then heat it to 900℃ at a rate of 25℃ / h and keep it warm for 6h, then heat it to 1450℃ at a rate of 20℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 10h at a heat preservation time, and get the final product by cooling in the furnace.
[0084] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.67g / cm 3 , water absorption rate is 8.5%.
[0085] Example 6 This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 40:60.
[0086] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0087] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0088] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0089] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0090] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0091] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 10℃ / h, then heat it to 900℃ at a rate of 25℃ / h and keep it warm for 8h, then heat it to 1450℃ at a rate of 20℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 2h at a heat preservation time, and get the final product by cooling in the furnace.
[0092] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.54g / cm 3 , water absorption rate is 11.3%.
[0093] Example 7 This embodiment provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 30:70.
[0094] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0095] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0096] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0097] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0098] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0099] Sintering: Place the formed sample in a tunnel kiln and heat it to 200℃ at a rate of 10℃ / h, then heat it to 900℃ at a rate of 20℃ / h and keep it warm for 6h, then heat it to 1450℃ at a rate of 20℃ / h, then heat it to 1600℃ at a rate of 20℃ / h for high-temperature calcination; sinter it for 6h at a heat preservation time, and get the final product by cooling in the furnace.
[0100] After testing, the performance indicators of the periclase forsterite composite material prepared in this embodiment are: volume density 2.63g / cm 3 , water absorption rate is 15.9%.
[0101] Comparative Example 2 This comparative example provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and magnesite and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and magnesite, wherein the mass ratio of magnesite flotation tailings and magnesite is 65:35.
[0102] Crushing: The magnesite is crushed and ball-milled until the particle size of the magnesite is less than 1 mm.
[0103] Mixing: Place the raw materials in a ball mill, add water until the liquid-solid ratio is 1.5:1, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0104] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0105] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0106] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0107] Sintering: Place the formed sample in a tunnel kiln and heat it to 200°C at a rate of 10°C / h, then heat it to 900°C at a rate of 25°C / h and keep it warm for 8h, then heat it to 1450°C at a rate of 20°C / h, and then heat it to 1600°C at a rate of 20°C / h for high-temperature calcination; sinter it for 8h at a heat preservation time, and cool it in the furnace to obtain the final product.
[0108] After testing, the performance indicators of the periclase forsterite composite material prepared in this comparative example are: volume density 2.55g / cm 3 , water absorption rate 23.5%.
[0109] Comparative Example 3 This comparative example provides a periclase-forsterite composite material prepared by using magnesite flotation tailings and hydrated magnesia bricks and a preparation method thereof, and the specific steps are as follows: Weighing: The raw materials required for weighing the sample are magnesite flotation tailings and hydrated magnesia bricks, wherein the mass ratio of magnesite flotation tailings to hydrated magnesia bricks is 65:35.
[0110] Crushing: crush and ball-mill the hydrated magnesia bricks until the particle size is less than 1mm.
[0111] Mixing: Place the raw materials in a ball mill, add water until the volume of the ball mill is two-thirds, and ball mill at a speed of 60r / min for 2h to form a uniformly mixed raw material.
[0112] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0113] Mud extrusion: The raw materials after pressure filtration are formed on the mud extruder and cut into periclase forsterite bricks.
[0114] Drying: Dry the formed raw materials in a drying kiln at 140°C for 48 hours.
[0115] Sintering: Place the formed sample in a high-temperature kiln, heat it to 200°C at a rate of 10°C / h, heat it to 1600°C at a rate of 20°C / h, keep it at that temperature for 4 hours, and sinter it.
[0116] After testing, the performance indicators of the periclase forsterite composite material prepared in this comparative example are: volume density 2.48g / cm 3 , water absorption rate is 19.1%.
[0117] The prepared periclase forsterite composite material was used to replace the magnesia sand in the magnesia brick for replacement experiment, and the prepared magnesia refractory brick was tested for performance. The volume density and apparent porosity of the sample were determined by Archimedes drainage method according to national standard GB / T2997-2000; a microcomputer-controlled fully automatic pressure testing machine (WHY-2000) was used, Shanghai Hualong Testing Instrument Co., Ltd.; the room temperature compressive strength of the sample was tested according to national standard GB / T5072-2008; the load softening temperature of the sample was tested according to GB / T 5989-2023, and the thermal shock resistance of the sample was tested according to GB / T 30873-2014. The test results are as follows: Table 2
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a periclase-forsterite composite material, characterized in that: include: The magnesite flotation tailings and the hydrated magnesia bricks are wet mixed and co-grinded, and then subjected to filter pressing, vacuum mud squeezing, drying and sintering; the mass ratio of the magnesite flotation tailings to the hydrated magnesia bricks is 60:40-90:
10.
2. The method for preparing the periclase-forsterite composite material according to claim 1, characterized in that: The mass ratio of the magnesite flotation tailings to the hydrated magnesium bricks is 65:35-87:
13.
3. The method for preparing the periclase-forsterite composite material according to claim 1, characterized in that: In the magnesite flotation tailings, the mass content of MgO is 38%~40%, and the mass content of SiO2 is 24%~26%; in the hydrated magnesia bricks, the mass content of MgO, Mg(OH)2 and MgCO3 is 80%~90% in terms of MgO.
4. The method for preparing the periclase-forsterite composite material according to claim 1, characterized in that: The method further comprises the step of pretreating the hydrated magnesia brick, wherein the pretreating comprises crushing and / or ball milling the hydrated magnesia brick.
5. The method for preparing the periclase-forsterite composite material according to claim 4, characterized in that: The particle size of the pretreated hydrated magnesia brick is less than 1 mm.
6. The method for preparing the periclase-forsterite composite material according to any one of claims 1 to 5, characterized in that: The wet mixing and grinding has a rotation speed of 25-150 r / min and a time of 0.5-4 h.
7. The method for preparing the periclase-forsterite composite material according to any one of claims 1 to 5, characterized in that: The sintering comprises the steps of performing secondary calcination, which comprises heating to 190-200°C at a rate of 13-15°C / h, then heating to 600-900°C at a rate of 20-25°C / h and keeping the temperature for 6-8h, then heating to 1350-1450°C at a rate of 25-30°C / h, and then heating to 1500-1650°C at a rate of 18-20°C / h for high temperature calcination; the calcination and heat preservation time is 2-10h.
8. The method for preparing the periclase-forsterite composite material according to claim 1, characterized in that: include: 1) Crushing: crush the hydrated magnesium bricks to a particle size less than 1mm; 2) Wet mixing and grinding: the crushed hydrated magnesia bricks are mixed with the magnesite flotation tailings and wet-grinded to obtain finely ground raw materials, with a grinding concentration of 60% to 80% and a grinding fineness of 200 to 400 meshes; 3) Dehydration: the wet mixed and ground raw materials are subjected to filter pressing to obtain a raw material filter cake after dehydration; 4) Vacuum mud extrusion: the raw material filter cake is formed and cut by a vacuum mud extruder to obtain a wet blank of a periclase-forsterite composite material; 5) Drying: drying the periclase-forsterite composite material wet blank to obtain a periclase-forsterite composite material blank; 6) Firing: sintering the periclase-forsterite composite material blank.
9. A periclase-forsterite composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the periclase-forsterite composite material prepared by the preparation method according to any one of claims 1 to 8 or the periclase-forsterite composite material according to claim 9 in the preparation of refractory materials.
Citation Information
Patent Citations
Method for preparing periclase-spinel composite material by coating process
CN112707719A
High-density periclase-forsterite composite refractory ceramic and preparation method thereof
CN113402286A
Two-step calcination method for preparing periclase-forsterite complex-phase refractory raw material
CN118388222A
Preparation method of periclase-forsterite complex-phase refractory raw material
CN118388223A
Method for synthesizing periclase-forsterite refractory material at low temperature
CN118745116A